1985
DOI: 10.1007/bf02007729
|View full text |Cite
|
Sign up to set email alerts
|

Antihepatoxic constituents ofGarcinia kola seeds

Abstract: Kolaviron, a fraction of defatted methanolic extract and biflavanones of Garcinia kola seeds significantly antagonized the lethal poisoning of mice with phalloidin. Garcinia biflavanones GB1, GB2 and kolaflavanone were isolated as the active constituents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
0
2

Year Published

1990
1990
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(95 citation statements)
references
References 7 publications
2
91
0
2
Order By: Relevance
“…Extraction of Kolaviron was achieved by the procedure previously described by Iwu (1985) [5], and modified by Braide (1991) [18]. Briefly, Garcinia kola seeds were peeled and air dried in the laboratory (25)(26)(27)(28) 0 C) and ground into powdered form.…”
Section: Extraction Of Kolavironmentioning
confidence: 99%
See 1 more Smart Citation
“…Extraction of Kolaviron was achieved by the procedure previously described by Iwu (1985) [5], and modified by Braide (1991) [18]. Briefly, Garcinia kola seeds were peeled and air dried in the laboratory (25)(26)(27)(28) 0 C) and ground into powdered form.…”
Section: Extraction Of Kolavironmentioning
confidence: 99%
“…Studies have also reported the use of this plant for the treatment of jaundice, high fever, purgative and as chewing stick. The plant also found usefulness in the treatment of stomach ache and gastritis [5,6]. The phytochemical compounds isolated from G. kola include oleoresin, tannins, saponins, alkaloids, cardiac glycosides.…”
Section: Introductionmentioning
confidence: 99%
“…Extraction of Kolaviron was achieved by the procedure previously described by Iwu (1985) and modified by Braide (1991). The outer cover of Garcinia kola seeds were peeled, sliced and air-dried in the laboratory (25-28 ºC) and grounded into powdered form.…”
Section: Methodsmentioning
confidence: 99%
“…The seed has also been shown to be useful as bronchodilator and antimicrobial in the treatment of bronchitis, throat troubles, heart diseases and urinary tract infections (Irvine, 1961;Iwu, 1985Iwu, , 1986Iwu, , 1993Iwu, Igboko, Elekwa & Tempesta, 1990). Ebana, Madunagu, Ekpe and Otung (1991) investigated the antimicrobial, antibacterial and antiviral properties while Iwu (1999) stated that Garcinia kola seed can be used as adaptogen and anti-inflammatory agent as well as in the cure of flu and influenza.…”
Section: Introductionmentioning
confidence: 99%
“…7, No. 2;2015 antioxidant properties (Ejele, 2010;Ejele & Akujobi 2011;Ejele, Nwaeze & Alinnor 2012a, Arekemase, et. al, 2012Daramola, Adegoke & Osonyinlusi,, 2012;A.…”
Section: Introductionmentioning
confidence: 99%